Suppression of the superconductivity in ultrathin amorphous Mo78Ge22 films observed by STM - Lotnyk, D.; Onufriienko, O.; Samuely, T.; Shylenko, O.; Komanický, V.; Szabó, P.; Feher, A.; Samuely, P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
In contact with a superconductor a normal metal modifies its properties due to Andreev reflection. In the current work the local density of states (LDOS) of superconductor–normal metal Mo78Ge22–Au bilayers are studied by means of STM applied from the Au side. Three bilayers have been prepared on silicate glass substrate consisting of 100, 10 and 5 nm MoGe thin films covered always by 5 nm Au layer. The tunneling spectra were measured at temperatures from 0.5 to 7 K. The two-dimensional cross-correlation between topography and normalized zero-bias conductance indicates a proximity effect between 100 and 10 nm MoGe thin films and Au lay-er where a superconducting gap slightly smaller than that of bulk MoGe is observed. The effect of the thinnest 5 nm MoGe layer on Au leads to much smaller gap moreover the LDOS reveals almost completely suppressed coherence peaks. This is attributed to a strong pair-breaking effect of spin-flip processes at the interface between MoGe films and the substrate.